The factors influencing the success of on-going agile software development projects - Tam, Carlos (2020)
We propose a model consisting of five people-factors that influence the success of on-going agile software development projects, success being measured in terms of cost, time, and customer satisfaction. After surveying 216 agile practitioners, the results obtained using SEM-PLS suggest that "team capability" and "customer involvement" are the main factors contributing to the success of on-going agile software development projects. These results were triangulated with the mixed-methods approach of a focus group, which supported the findings. By knowing which factors are truly important to achieve success, managers and teams will be able to establish priorities, thereby improving project outcomes. We address this matter, along with research limitations and future work.